Pathways: A graphic meditation. Issue 2 (1st December 2016) - Burdock, Maureen
Women's stories. For a decade, I created a series of graphic fables in which women protagonists from different cultures work with their communities to eliminate gender-based violence. McFarland anthologized that series, Feminist Fables for the Twenty-First Century, in 2015. In my current work, I am continuing to focus on women's stories; specifically, I am developing autohistoriographic1 narratives, in which my own stories are intimately intertwined with the stories of my female ancestors and with cultural and historical themes. I created Pathways in the space between completing Feminist Fables and beginning this new work. Pathways shows movement towards a deeper understanding of my own stories and the creation of new lines of thought in connection with memories, ghosts, and with the more-than-human world. Drawing – a process of making lines that connect and intersect to create image-stories – is itself an act of finding or forging new pathways.